EFFICIENCY OF ENDOVASCULAR MYOCARDIAL REVASCULARIZATION AS A «BRIDGE» TO HEART TRANSPLANTATION IN PATIENTS WITH ISCHEMIC HEART FAILURE - A. B. Mironkov; S. A. Sakhovsky; I. G. Ryadovoy; B. L. Mironkov (Вестник трансплантологии и искусственных органов)
Aim: to estimate effi ciency of endovascular myocardial revascularization in patients with ischemic chronic heart failure, potential candidates for heart transplantation.Materials and methods. Survival of 108 patients with ischemic heart disease complicated by chronic heart failure (CHF) after performance of endovascular myocardial revascularization by percutaneous coronary intervention (PCI) is presented. The observation period composed 32.79 ± 6.2 (from 3 to 126) months, age from 33 to 72 (58.9 ± 0.64) years, 102 men, 6 women. Left ventricular (LV) ejection fraction was 34.9 ± 0.6%, EDV 249.75 ± 4.9 ml, ESV 163.27 ± 3.7 ml, mitral regurgitation 1.51 ± 0.07 points. 73% of patients had NYHA Class III CHF, 27% had NYHA Class IV CHF. Duration and quality of life after revascularization were determined. In 2–3 days after PCI dynamics of LV ultrasound parameters were estimated.Results. At the time of the end of our research 88 from 108 patients (81%) were alive, including 18 patients who underwent heart transplantation (HT). Repeated revascularization was carried out to 19 (17%) patients. 20 patients died: 16 patients with cardiovascular disorders (15%, including 4% of stroke), 3 with pulmonary embolism and 1 with oncological disease. Survival of 90% of the patients composed 4.5 years, 50% survival composed 9 years. At the time of the end of our research the maximum observation period was equal to 126 months. The duration from the fi rst PCI to HT composed from 7.5 to 105 months, mean value – 37 ± 7.5 months. Average life expectancy after HT composed 54.9 ± 24.4 months. Life expectancy from the fi rst PCI composed 87.5 ± 36.9 months. All patients of this group were alive by the time of the end of this research.Conclusion. Endovascular revascularization in patients with ischemic heart failure in 20% of cases can serve as «bridge» to HT, in 50% of cases it can be considered as an alternative to heart transplantation.